Return and Risk of Stock Investment in Finance Sector - Sibarani, Bintang Berliana (Universitas Mercu Buana, 2024)
The goal of this study is to offer investors with information to aid in deciding how to allocate their investment dollars. Investment risk results from the discrepancy between the projected return and the actual return; unfavorable risk is brought on by uncertain situations. If macroeconomic conditions are favorable, inflation is under control, exchange rates improve, and interest rates are low, investors will feel secure. Investors look for a return on their investments, either in the form of dividends or capital gains. Investors' behavior toward risk have an impact on investment decisions that are based on risk and return. The five economic circumstances studied in this study are as follows: (1) recession; (2) moderate recession; (3) normal; (4) good; and (5) excellent. The result of this study is investment at BNGA (PT CIMB NIAGA, Tbk) and BBCA (PT BANK CENTRAL ASIA, Tbk) as a high return and low risk. These stocks are recommended in any economic situation. If an investor fits the suggested risk-taker profile, they should consider investing in BNGA; otherwise, they should consider BBCA.